Impact of the COVID-19 Pandemic on Car-Sharing in Poland - Gorzelanczyk, Piotr; Kalina, Tomas; Jurkovic, Martin (Communications - Scientific Letters of the University of Zilina, 2022)
The number of cars on Polish roads is increasing year by year. Currently, Poland is in second place in Europe in terms of the number of cars per 1000 inhabitants [1]. This causes problems in finding a place to park. In addition, during the pandemic, there was a problem with semis, which caused a sharp increase in the price of used cars and longer waiting times for new vehicles. The aim of this article is to find out the opinion of Polish residents on the Car-Sharing service during the COVID-19 pandemic and how the pandemic has affected Car-Sharing not only in Poland, but also in Europe as a whole. For this purpose, a survey was conducted.
Keywords: car-sharing; Poland; vehicle; COVID-19; pandemic